2002
DOI: 10.1653/0015-4040(2002)085[0572:iomdom]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Male Diet on Male Mating Success and Longevity and Female Remating in the Mediterranean Fruit Fly (Diptera: Tephritidae) Under Laboratory Conditions

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 19 publications
3
59
0
1
Order By: Relevance
“…An additional 10 Ð20 ßies were prepared per group as "extras" to replace any dead or weak individuals at the time of release. The latter tests also necessitated marking of one of the two released groups of males (randomized) for the purpose of subsequent identiÞcation, which was accomplished by chilling and applying a small dot of enamel paint to the mesonotum ϳ24 h before testing, a routinely used procedure from which males recover quickly without any detectable effect on their subsequent behavior (Shelly and Kennelly 2002).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional 10 Ð20 ßies were prepared per group as "extras" to replace any dead or weak individuals at the time of release. The latter tests also necessitated marking of one of the two released groups of males (randomized) for the purpose of subsequent identiÞcation, which was accomplished by chilling and applying a small dot of enamel paint to the mesonotum ϳ24 h before testing, a routinely used procedure from which males recover quickly without any detectable effect on their subsequent behavior (Shelly and Kennelly 2002).…”
Section: Methodsmentioning
confidence: 99%
“…Shelly et al (2001) further determined that females were more attracted to aggregations of protein-fed males than those of protein-deprived males in a test of long-distance attraction. However, the apparent association between adult diet and reproductive success remains somewhat unclear, because other studies have not found any mating advantage for protein-fed over sugar-fed laboratory males (Shelly andKennelly 2002, Shelly andMcInnis 2003). Furthermore, when extending their investigation to sterile ßies, observed a dietrelated trade-off between male mating success and survival , Jácome et al 1999, with prior protein-fed sterile males suffering very high mortality when starved.…”
mentioning
confidence: 96%
“…Due to its commercial relevance, many studies focused on the development and improvement of different control strategies. Some of them are based on the use of biological competitors (Headrick and Goeden 1996) or sterile adults, as in the Sterile Insect Technique (SIT, Shelly and Kennelly 2002;Shelly and McInnis 2003;Shelly 2005), others on chemicals, such as the mass trapping (Jang et al 1989(Jang et al , 1994Heath et al 1991;Cossè et al 1995;Katsoyannos et al 1997;Papadopoulos et al 2001). Both SIT and mass trapping are more effective when they involve the activation of the olfactory system, since odorants can be used as efficient species-specific attractants.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Muller et al (1997) reported that the mortality rates of C. capitata decreased when the adults were fed on protein diets. Others authors do not show any strict link between the amount of protein ingestion in their adult phase and longevity (Shelly and Kennelly, 2002;Shelly and McInnis, 2003). Despite the fact that longevity can be an important parameter in evaluating the quality of any diet (Chang et al, 2001), the most important considerations for large scale commercial producers are that the females produce large numbers of viable eggs near the peak phase of ovipositioning and that the males are active and able perform copulation so that there will be no drop in fertility.…”
Section: Resultsmentioning
confidence: 98%